Mapeamento de solos através do caráter espectral, da rede de drenagem e da vegetação - Marchetti, D.a.; Garcia, G.j. [UNESP] (Universidade de São Paulo; Escola Superior de Agricultura, 1990)
This study puts together three different methodologies that utilize Remote Sensing Techniques for the study of soils. The soils of the selected area were studied by their spectra parameters and analysed through satellite images processed in an appropriate equipment. The drainage indices were correlated to their respective soils. The well known relationship between types of cerrado vegetation and associated soils were also studied. For each situation a soil map was prepared; those maps showed a reasonable relationship with the ground truth. Wen these informations were put together in a single map, the relationship with the reference soil map was highly significant, showing the applicability of the methodology.

O presente trabalho reuniu três metodologias conhecidas para o estudo de solos, todas associadas às técnicas de sensoriamento remoto. Para uma mesma área, os solos foram relacionados aos seus parâmetros espectrais obtidos digitalmente de imagens de satélite; os índices de drenagem da área foram também relacionados aos respectivos solos; a conhecida relação entre tipos de cerrado e respectivos solos suporte foi também estudada. Para cada situação foi preparado um mapa de solos, que se aproximava do mapa já existente. Quando as informações de tais mapas foram agregadas em um único mapa, a aproximação com o mapa de controle foi altamente satisfatória evidenciando a aplicabilidade da metodologia.
Soil mapping through spectra parameters, drainage network and vegetation
Keywords: soils; mapping; satellite; solos; mapeamento; sensoriamento remoto